2007
DOI: 10.17221/2317-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a clinoptilolite supplement in pig diets on performance and serum parameters

Abstract: ABSTRACT:The effects of clinoptilolite in pig's diets were examined on sixty Landrace × Yorkshire crossbred pigs of both sexes divided into two groups: 1. control group, with basal diets; 2. treatment, with basal diets supplemented with 5 g clinoptilolite per 1 kg diet (Cp group). Feed and water were available ad libitum. Individual live weights were recorded on days 45, 90 and 135 of the experiment. Feed consumptions were recorded weekly. Blood was drawn from the anterior vena cava of each pig at day 135 for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
2
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 17 publications
5
31
2
5
Order By: Relevance
“…These studies documented that even long-term feeding did not affect levels of total serum protein, albumin and mineral elements in pigs Alexopoulos et al, 2007). Some studies have reported changes in glucose, cholesterol and AST levels (ConcepcionRosabal et al, 1997;Alexopoulos et al, 2007;Prvulovic et al, 2007). The present study did not find any changes in Fe distribution and haematological parameters in piglets.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…These studies documented that even long-term feeding did not affect levels of total serum protein, albumin and mineral elements in pigs Alexopoulos et al, 2007). Some studies have reported changes in glucose, cholesterol and AST levels (ConcepcionRosabal et al, 1997;Alexopoulos et al, 2007;Prvulovic et al, 2007). The present study did not find any changes in Fe distribution and haematological parameters in piglets.…”
Section: Discussionsupporting
confidence: 50%
“…The structure and physical-chemical characteristics of these clay minerals and kaolin, which is a phyllosilicate mineral, are similar . A significant increase in the body weight gain and improved conversion of feed containing clay minerals has been shown by numerous studies (Pond et al, 1981(Pond et al, , 1988Vrzgula et al, 1982;Bartko et al, 1983;Pond and Yen, 1987;Castro and Iglesias, 1989;Cabezas et al, 1991;Papaioannou et al, 2004;Chen et al, 2005;Kolacz et al, 2005;Papaioannou et al, 2005;Alexopoulos et al, 2007;Prvulovic et al, 2007). Naturally, their effect on the efficiency of animals is associated with the type, physicochemical and structural qualities, purity and proportion of these minerals in the diet (Pond and Yen, 1987;Pond et al, 1988;Papaioannou et al, 2004Papaioannou et al, , 2005, and by the age of animals (Papaioannou et al, 2004;Alexopoulos et al, 2007).…”
Section: Discussionmentioning
confidence: 92%
“…Nevertheless, diets supplemented with a higher proportion of such adsorbents are also voluntarily ingested by animals (Castro and Elias, 1978;Vrzgula et al, 1982;Bartko et al, 1983;Castro and Iglesias, 1989), and do not exert any adverse effect on their growth and performance (Castro and Elias, 1978;Castro and Iglesias, 1989). Many studies have documented significant improvements in body weight gain and feed conversion after supplementation of a diet with clay minerals (Pond et al, 1981;Vrzgula et al, 1982;Bartko et al, 1983;Pond and Yen, 1987;Pond et al, 1988;Castro and Iglesias, 1989;Cabezas et al, 1991;Papaioannou et al, 2004Papaioannou et al, , 2005Chen et al, 2005;Kolacz et al, 2005;Alexopoulos et al, 2007;Prvulovic et al, 2007;Trckova et al, 2009). …”
Section: Adsorption Capacity and Effects Of Clay Mineralsmentioning
confidence: 99%
“…Natural zeolite clinoptilolite has been reported to be nutritionally inert adsorbent and non-toxic to animals [4,5] which make clinoptilolite very advantageous. Several studies demonstrated that clinoptilolite supplementation was well tolerated by animals such as it resulted significant feed conversion and promoted biomass production, weight gain and animal health [6][7][8][9][10][11]. Clinoptilolite was used to protect animals from feed-originated toxins by adsorbing toxic compounds in gastrointestinal tract and by preventing their passage to circulatory system [12][13][14].…”
Section: Introductionmentioning
confidence: 99%